Angiotensin II Regulates microRNA-132/-212 in Hypertensive Rats and Humans - Tilde V. Eskildsen (International Journal of Molecular Sciences, 2013)
MicroRNAs (miRNAs), a group of small non-coding RNAs that fine tune translation of multiple target mRNAs, are emerging as key regulators in cardiovascular development and disease. MiRNAs are involved in cardiac hypertrophy, heart failure and remodeling following cardiac infarction; however, miRNAs involved in hypertension have not been thoroughly investigated. We have recently reported that specific miRNAs play an integral role in Angiotensin II receptor (AT1R) signaling, especially after activation of the Gαq signaling pathway. Since AT1R blockers are widely used to treat hypertension, we undertook a detailed analysis of potential miRNAs involved in Angiotensin II (AngII) mediated hypertension in rats and hypertensive patients, using miRNA microarray and qPCR analysis. The miR-132 and miR-212 are highly increased in the heart, aortic wall and kidney of rats with hypertension (159 ± 12 mm Hg) and cardiac hypertrophy following chronic AngII infusion. In addition, activation of the endothelin receptor, another Gαq coupled receptor, also increased miR-132 and miR-212. We sought to extend these observations using human samples by reasoning that AT1R blockers may decrease miR-132 and miR-212. We analyzed tissue samples of mammary artery obtained from surplus arterial tissue after coronary bypass operations. Indeed, we found a decrease in expression levels of miR-132 and miR-212 in human arteries from bypass-operated patients treated with AT1R blockers, whereas treatment with β-blockers had no effect. Taken together, these data suggest that miR-132 and miR-212 are involved in AngII induced hypertension, providing a new perspective in hypertensive disease mechanisms.